2018
DOI: 10.1002/ejoc.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Dynamic Combinatorial Libraries Using Hydrazone‐Functionalized Surface Mimetics

Abstract: Dynamic combinatorial chemistry (DCC) represents an approach, whereby traditional supramolecular scaffolds used for protein surface recognition might be exploited to achieve selective high affinity target recognition. Synthesis, in situ screening and amplification under selection pressure allows the generation of ligands, which bear different moieties capable of making multivalent non‐covalent interactions with target proteins. Generic tetracarboxyphenyl porphyrin scaffolds bearing four hydrazide moieties have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Changes in library composition upon introduction of the target are thus exploited to probe favorable interactions. DCC has been barely used in peptide and peptidomimetic chemistry but few example are reported: [7,8] to assemble peptides fragments into supramolecular 3D protein‐like structure, [9–11] to create peptide bonds between amino acids surrogates [12,13] or to graft side chains either on a flexible polymer backbone [14,15] or a rigid organic scaffold [16–18] . The covalent reversible functionalization of a well‐ordered peptide scaffold has been also reported [19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in library composition upon introduction of the target are thus exploited to probe favorable interactions. DCC has been barely used in peptide and peptidomimetic chemistry but few example are reported: [7,8] to assemble peptides fragments into supramolecular 3D protein‐like structure, [9–11] to create peptide bonds between amino acids surrogates [12,13] or to graft side chains either on a flexible polymer backbone [14,15] or a rigid organic scaffold [16–18] . The covalent reversible functionalization of a well‐ordered peptide scaffold has been also reported [19] .…”
Section: Introductionmentioning
confidence: 99%
“…DCC has been barely used in peptide and peptidomimetic chemistry but few example are reported: [7,8] to assemble peptides fragments into supramolecular 3D protein-like structure, [9][10][11] to create peptide bonds between amino acids surrogates [12,13] or to graft side chains either on a flexible polymer backbone [14,15] or a rigid organic scaffold. [16][17][18] The covalent reversible functionalization of a well-ordered peptide scaffold has been also reported. [19] Combination of such a folded scaffold with dynamic combinatorial method has never been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…DCC has been barely used in peptide and peptidomimetic chemistry but few example are reported: 7,8 to assemble peptides fragments into supramolecular 3D protein-like structure, [9][10][11] to create peptide bonds between amino acids surrogates 12,13 or to graft side chains either on a flexible polymer backbone 14,15 or a rigid organic scaffold. [16][17][18] The covalent reversible functionalization of a wellordered peptide scaffold has been also reported. 19 Combination of such a folded scaffold with dynamic combinatorial method has never been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although pioneering studies demonstrated the possibility of ribosome-assisted coupling of amino acids with non-natural backbones, [4][5][6][7] in vitro directed evolutionary approaches 8 are not routinely available for searching and optimization of fundamentally xenobiotic surface mimetic structures. [9][10][11] Four major experimental chemical approaches and their combinations have been applied to address this problem: (i) screening of large surface mimetic libraries, 10,12,13 (ii) topdown mutational design based on known ligands, [14][15][16][17][18][19][20][21] (iii) bottom-up design and assembly starting from structural hypotheses, 3,[22][23][24][25][26][27][28][29][30][31] and (iv) the fragment-centric system chemistry approach leading to self-assembling ligands. 32 Recent theoretical and experimental results strongly support that fragment-centric design built on recognition elements of reduced structural complexity is highly promising for the construction of surface mimetic ligands.…”
Section: Introductionmentioning
confidence: 99%